Keputusan Investasi dalam Perspektif Keuangan: Hubungan Literasi, Risiko, dan Locus of Control pada Mahasiswa - Fatima Zahara; Nera Marinda Machdar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Planning investment in personal financial management, especially among students, is very important. Investment serves as one way to learn to manage finances, both for current and future needs. However, the lack of understanding of investment decision making often makes students vulnerable to fraud, especially because they are tempted by tempting investment offers. This study aims to identify and analyze theories that discuss the influence of financial literacy, risk perception, and financial behavior on investment decisions, with locus of control as a moderating variable. This study refers to signal theory and prospect theory, and uses a literature review approach. In this study, related variables and previous research results are discussed theoretically. The research findings show differences in the influence of financial literacy, risk perception, and financial behavior on investment decisions. Moderation by locus of control is proven to have a significant role, although there is no clear agreement from the research findings. This study contributes by offering deeper insights to explain ongoing related phenomena.